(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The article describes the role and importance of the Universal Declaration of Human Rights and the Constitution of the Republic of Uzbekistan as the legal basis of guarantees of the right to citizenship. It was also emphasized that human rights are an important constitutional institution and their provision and guarantees in a democratic-legal state.